The Effect of Motivation, Work Discipline and Work Environment on Employee Job Satisfaction - Hanif, Muhammad Abhirama; Ariani, Misna; Arrywibowo, imam (Universitas Syiah Kuala, 2025)
The purpose of this study was to determine the effect of Motivation, Work Discipline and work environment on job satisfaction of employees of the Kariangau Balikpapan Health Center UPTD. The type of research used is quantitative research. The sampling technique in this study used purposive sampling with a population of 43 employees, so the sample taken in this study of the Kariangau Balikpapan Health Center UPTD was 30 employees who would be used as the sample size of the study. The data collection method was carried out by distributing questionnaires. This study uses multiple linear regression with the help of SmartPLS in processing data. The results of this study indicate that the Motivation variable has an effect on the job satisfaction of employees of the UPTD Kariangau Balikpapan Health Center, the Work Discipline variable has an effect on the job satisfaction of employees of the UPTD Kariangau Balikpapan Health Center, and the Work Environment variable has an effect on the job satisfaction of employees of the UPTD Kariangau Balikpapan Health Center.